2017
DOI: 10.1163/18759866-08601004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics and systematic revision of the south-eastern Australian Helicarionidae (Gastropoda, Stylommatophora)

Abstract: The south-eastern Australian helicarionid clade currently comprises six genera of snails and semislugs united by genital characters, including an epiphallic flagellum that produces a spiraling, spinose spermatophore, the absence of an epiphallic caecum, and the presence of at most a very short vagina. We comprehensively revise the taxonomy of this group based on comparative analyses of key morphological features and mitochondrial markers COI and 16S, revise the placement of several species described recently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Although genetic distances per se are poor taxonomic indicators (Dasmahapatra et al, 2010;Davison et al, 2009;Köhler, 2007;Köhler & Johnson, 2012), the maximum distances between any two Asperitas samples were well within the range of intraspecific mitochondrial differentiation in the closely related genus Everettia from Borneo (Liew et al, 2009; Figure 2). These distances are also comparable with the amounts of intraspecific genetic distances recently observed in several helicarionid genera from Australia belonging to the same superfamily (Hyman & Köhler, 2018, 2019Hyman et al, 2017) as well as in other stylommatophorans (for an overview of intra-and interspecific COI distances in various stylommatophoran groups refer to Koch et al 2020; Table S3). Moreover, our examinations revealed that the reproductive anatomy in individuals from Timor, Bali, and Flores, which represent several nominal species, was virtually identical.…”
Section: The Taxonomic Diversity Of Asperitas On Timorsupporting
confidence: 84%
“…Although genetic distances per se are poor taxonomic indicators (Dasmahapatra et al, 2010;Davison et al, 2009;Köhler, 2007;Köhler & Johnson, 2012), the maximum distances between any two Asperitas samples were well within the range of intraspecific mitochondrial differentiation in the closely related genus Everettia from Borneo (Liew et al, 2009; Figure 2). These distances are also comparable with the amounts of intraspecific genetic distances recently observed in several helicarionid genera from Australia belonging to the same superfamily (Hyman & Köhler, 2018, 2019Hyman et al, 2017) as well as in other stylommatophorans (for an overview of intra-and interspecific COI distances in various stylommatophoran groups refer to Koch et al 2020; Table S3). Moreover, our examinations revealed that the reproductive anatomy in individuals from Timor, Bali, and Flores, which represent several nominal species, was virtually identical.…”
Section: The Taxonomic Diversity Of Asperitas On Timorsupporting
confidence: 84%
“…There are several genital characters that are seen in all or most of the extreme helicarionid semislugs. All five genera examined herein, and additional extreme semislug genera Parmellops and Cucullarion , have a unilobed ovotestis and lack a vagina (Hyman et al, 2017; Hyman & Ponder, 2016). The only exceptions are Thularion semoni and T. stanisici , which have a distinct vagina.…”
Section: Discussionmentioning
confidence: 98%
“…DNA extraction, PCR and sequencing were undertaken as described by Hyman et al (2017). Electropherograms were corrected for misreads and forward and reverse DNA strands were merged into one sequence file using CodonCode Aligner v. 3.6.1 (CodonCode Corp., Dedham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Electropherograms were corrected for misreads and forward and reverse DNA strands were merged into one sequence file using CodonCode Aligner v. 3.6.1 (CodonCode Corp., Dedham, MA). Sequences of previous helicarionid studies (Hyman et al, 2007;Hyman et al, 2017) were retrieved from GenBank and included in our dataset while all newly produced sequences have been deposited in GenBank under the accession numbers KY769386-KY769398.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation